Electromechanical Analogies for the Theory of Consolidation - Uklejewski, R.; Krakowski, M. (Engineering Transactions, 1982)
The electromechanical analogies between one-dimensional systems with distributed parameters are examined, applying Firestone’s system of electromechanical analogies, by means of dimensional analysis. The existence of such analogies for the theore of consolidation is provede: it constitutes the basis to the application of some methods and concepts from electrotechnics in this theory. As an example of such application, an algorithm of the method of determination of elastic coefficients of a porous medium is presented.